Bioinformatic Test and Pharmacokinetic Profile Prediction of Gnetin-C Compound in Melinjo (Gnetum gnemon L.) Seeds Toward Colorectal Cancer - Kenyori, Ivana Kinanti; Febriansah, Rifki (Indonesian Journal of Cancer Chemoprevention, 2024)
Cancer is one of the unresolved health problems in the world, including Indonesia. One of the most common types of cancer is colorectal cancer. Melinjo (Gnetum gnemon L.) is one of Indonesian local commodities which has many benefits including its potential to be developed as an anticancer agent. Through bioinformatics and molecular docking technology, the aim of this study was to investigate the functions of gnetin-C from melinjo against colorectal cancer. PkCSM database were used to search the ADMET (absorption, distribution, metabolism, elimination and toxicity) properties and stitch-string database were used to identify common genes related to colon cancer. During identification of colon cancer related genes, STAT3 protein showed the highest degree score. Furthermore, molecular docking was carried out to find out the interaction between the STAT3 protein and gnetin c compound found in melinjo seeds. From the docking stage, the pose with the best affinity energy was obtained with a docking score of 1,966 kcal/mol. this shows that the compound gnetin c has the potential to be used as a new anticancer agent from natural ingredients.Keywords: Melinjo, Gnetum gnemon, colon cancer, bioinformatics, molecular docking.